Investigação da estabilidade e da qualidade de energia no ponto de conexão de um inversor trifásico com filtro LCL operando de forma conectada ou ilhada sujeito a variações de carga - Zamodzki, Rafael (2017)
The operation of distributed generation units (DGUs) is a relatively recent issue in the Brazilian energetic scenario. The connection of these units to the grid, as their disconnection are being approached in recent researches worldwide. It is necessary that the electrial power delivered to the grid and to the power has some levels of quality so the consumer may be well attended even in contingence situations. Another necessary caution is related to the control systems involved, so they operate without degrade the power quality. At this point, this work proposes the stability and power quality analysis in the point connection of a distributed generation unit to the grid and to the load or just to the load, both situations through LCL (inductive-capacitive-inductive) filter. This kind of filter has an impedance that is characterized by resonance peak near to its cut-off frequency. It is necessary to damp this peak in order that the sytem is not lead to instability. In this Master Thesis, some cases are proposed to be analyzed. These cases differ one from another because of the controlled variable, by the kind of operation of the system and by the damping technique that is used. In the case of the grid and load-tied inverter, the analyzed cases are those in which the first or second filter inductor current is the controlled variable. For the case in which the inverter is just feeding the local load, the controlled variable is the LCL filter capacitor voltage. All of these cases are evaluated by operating with none resonace damping, passive damping or active damping. Beyond this, for these scenarios, there is the parameters variation of the RL (resistive-inductive) load in order to check which is the influence of the load variations in the system stability and in the power quality at the connection point. The stability analysis are performed through Bode diagrams and pole-zero maps of the system. The power quality analysis is carried out by means of experimental results obtained in an experimental bench. It is verified through the results that in terms of power quality, there is not significantly changes by controlling different variables in the grid-tied mode. Furthermore, other factors, beyond the controlled variable, the kind of damping technique and the criticak frequency influence in the instability of the system due to the resonance. Through the analysis, it is oberserved that a well-adjusted PI (proporcional-integral) controller may offer robustness to the system under load parameter variations and consquent controlled variable variations. It is also noted that for the stand-alone case, the THDi and the THDv (Total Harmonic Distortions of Current and Voltage) are low, providing good power to the local load fed by the system.